Pengaruh Komunikasi Internal dan Kerjasama Tim terhadap Kinerja Pegawai pada Dinas Komunikasi dan Informatika Kabupaten Karawang - Robby Darmawan; Sungkono Sungkono; Maman Mulya Karnama (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze the impact of communication and teamwork on employee performance at the Karawang Regency Communication and Informatics Office. The results of the observation show that one-way communication often occurs, hindering the delivery of information and affecting work effectiveness. In addition, the lack of teamwork causes delays in completing tasks and reduces employee performance. This study uses a quantitative method with a verification approach to measure and test the relationship between communication factors, teamwork, and employee performance significantly. Data were collected through questionnaires distributed to Karawang Communication and Informatics Office employees. The results showed that internal communication and teamwork have a positive and significant effect on employee performance. These findings suggest that increasing positive internal communication and teamwork can substantially improve the performance of Karawang Communication and Informatics Office employees.